Determining optimal fluid and air leak cut off values for chest drain management in general thoracic surgery - Mesa-Guzman, Miguel; Periklis, Perikleous; Niwaz, Zakiyah; Socci, Laura; Raubenheimer, Hilgardt; Adams, Ben; Gurung, Lokesh; Uzzaman, Mohsin; Lim, Eric (Journal of Thoracic Disease; Vol 7, No 11 (November 28, 2015): Journal of Thoracic Disease, 2015)
Background: Chest drain duration is one of the most important influencing aspects of hospital stay but the management is perhaps one of the most variable aspects of thoracic surgical care. The aim of our study is to report outcomes associated with increasing fluid and air leak criteria of protocol based management. Methods: A 6-year retrospective analysis of protocolised chest drain management starting in 2007 with a fluid criteria of 3 mL/kg increasing to 7 mL/kg in 2011 to no fluid criteria in 2012, and an air leak criteria of 24 hours without leak till 2012 when digital air leak monitoring was introduced with a criteria of